2021
DOI: 10.34117/bjdv7n2-030
|View full text |Cite
|
Sign up to set email alerts
|

Hastes De Gladíolo Cultivadas Sob Telas De Sombreamento E Doses De Cama De Aviário / Gladiolus Rods Cultivated Under Shade Screens and Avian Bed Doses

Abstract: Hastes de Gladíolo cultivadas sob telas de sombreamento e doses de cama de aviário Gladiolus rods cultivated under shade screens and avian bed doses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…At harvest, the following morphological measurements were performed (FERRON et al 2021): length of the largest leaf (distance, in centimeters, between the soil surface and the apex of the highest leaf); number of buds per floral spike; plant height (distance, in centimeters between the soil surface and the insertion of the apical floral bud); length of the floral ear (distance, in centimeters, between the insertion of the basal floral bud and apical); and rod diameter (cm).…”
Section: Methodsmentioning
confidence: 99%
“…At harvest, the following morphological measurements were performed (FERRON et al 2021): length of the largest leaf (distance, in centimeters, between the soil surface and the apex of the highest leaf); number of buds per floral spike; plant height (distance, in centimeters between the soil surface and the insertion of the apical floral bud); length of the floral ear (distance, in centimeters, between the insertion of the basal floral bud and apical); and rod diameter (cm).…”
Section: Methodsmentioning
confidence: 99%
“…The shade nets reduce the direct incidence of sunlight, thus, causing a reduction in air temperature. In addition, colored nets provide physical protection by solar radiation filtration, promoting specific light-regulated plant responses (Santos, 2014;Ferron et al, 2021).…”
Section: Capter 136mentioning
confidence: 99%
“…Shade nets reduce the direct incidence of sunlight, thus, causing a reduction in air temperature. In addition, colored nets provide physical protection by solar radiation filtration, promoting specific light-regulated plant responses (Santos, 2014;Ferron et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, technicians and field extensionists still do not have enough support to indicate the best management or growing season for farmers in that region. This is because little is known about the growth, development and quality of gladiolus flowers produced at different times of the year, although some initial experiments in Paraná (Ferron et al, 2021) showed a risk of loss of the floral stem due to extreme temperatures and water deficit during warmer periods.…”
Section: Introductionmentioning
confidence: 99%